Gaya Hidup, Status Gizi dan Stamina Atlet pada Sebuah Klub Sepakbola - Mirza Hapsari Sakti Titis Penggalih, Emy Huriyat (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: Indonesian Sport’s achievement is decline in ASEAN level. It has been being our consideration for professional athletes in Indonesia. Nutrition is one of major factor that contribute a lot of sports performance in athletes. Carbohydrates, protein, fat, fibber, fluid and others micro nutrient intakes are important to maintain health, training adaptation, and improve performance athlete weather neither in training session nor in match day.Objective: The aim of this research was to know about lifestyle, nutritional status and athlete’s endurance in a soccer club.Method: This research was an observational research with cross-sectional design. This research was held in Gelora Remaja Persatuan Sepakbola Kabupaten Pasuruan (PerseKabPas). Research subject were athletes who train under this club and follow the research. Data collected through interview (nutritional intake and lifestyle); anthropometry measurements (weight, height, and skin fold); and VO2max measurement. Data was displayed descriptively and analysed with regression and chi-square technique.Result: Sixteenth respondents involved in this research. Athletes were never drinks alcohol (0 glass/ d), coffee (0, 4 glass/d), smoke (1 cigarette/d); tea consumption (1, 75 glass/d) and three time eating pattern. Daily activities were sleep (7, 63 h/d); training (3, 5 h/d); Work (3, 06 h/d) and study (1, 69 h/d). Nutritional intake for calories (daily, pre and post match day) respectively were 1559,85 cal; 1417,89 cal and 1708,07 cal. Protein intakes were 57,41 gr; 44,18 gr; 51,32 gr. Fat intakes were 31,12 gr; 30,86 gr; 33,48 gr. Carbohydrate intakes were 229,43 gr; 215,69 gr; 274,73 gr. Body Mass Index and body fat were 20,93 kg/m2 and 11, 05%. VO2Max measurement was 38, 13. The regression and chi-square technique shown that age, BMI, body fat independently didn’t give any positive and significant relation to athlete’s endurance (P>0,05), but BMI and body fat together; calories intake; lifestyle and physical activities gave a positive and significance relation to athletes endurance (P<0,05).Conclusion: Nutritional intake in this research was fa0r below the recommended nutritional needs for adult and national athletes. Athlete’s lifestyle has been applying the recommendation from International Olympic Committee; Nutritional status was normal (BMI and body fat). Athlete’s endurance was far below national athletes of endurance standard. There were a positive and significance relation between calories intake, lifestyle, physical activities and nutritional status to athlete’s endurance.Keywords: lifestyle, nutritional status, endurance, soccer